The Evolution of Israel's Religion from Abraham to Pre-Exilic and Its Significance for Christians - Suyadi Tjhin; Leonardo C. Dendeng (UIN Sunan Gunung Djati, 2022)
This article examines the evolution of Israel's religion from the Abrahamic Pre-exilic (approx. 2100-586 BC). The main data of this research is a literature study with a qualitative methodology through an Integrative Critical Analysis (ICA) approach to achieving the aims or objectives of the research. The conclusion or research results obtained are that the evolution of Israel's religion occurred not only in an applicative manner but also substantively. The evolution of Israel's religion can be said to be inseparable from the population, natural, socio-political, marriage, or family factors, where religion is the ultimate concern for survival, aligning life with the universe (aligning one's self with the universe), appeasing the gods including Baal, Asherah, Molok, and others to get their favor (how to placate the deities and secure their favor) with the background of the principle that obedience can be a blessing and disobedience can be a curse. Its significance for Christians is that Israel's religion and Christianity have historical and theological links to deepen understanding of the Bible; as a mirror of faith and Christian life; and how Christians should practice their religion in a pluralist society and the midst of pluralism.